Les services écosystémiques comme outils d’aide à la décision et de communication pour les parcs naturels régionaux. L’exemple du parc Scarpe-Escaut - Leslie Carnoye (Développement Durable et Territoires)
The purpose of this paper is to question the meaning of the ecosystem services (ES) approach and its usefulness for regional natural parks. The field work realized in the Park Scarpe-Escaut includes: an observational experience in a research project aiming at valuing several ES on the territory, 10 semi-directive interviews and the analysis of the park’s management documents. The study concludes that ES have important limits, whether they are considered as decision-aid tools or as communicational tools. The case of the park Scarpe-Escaut is interesting because it challenges the belief in the efficacy of ES and monetary arguments for biodiversity protection, spread by the new environmental pragmatists.